Long non-coding RNAs in colorectal cancer: Novel oncogenic mechanisms and promising clinical applications. (28th April 2021) - Yang, Yufei; Yan, Xuebing; Li, Xinxiang; Ma, Yanlei; Goel, Ajay
Abstract: Colorectal cancer (CRC) is the third most common malignancy and ranks as the second leading cause of cancer-related deaths worldwide. Despite the improvements in CRC diagnosis and treatment approaches, a considerable proportion of CRC patients still suffers from poor prognosis due to late disease detections and lack of personalized disease managements. Recent evidences have not only provided important molecular insights into their mechanistic behaviors but also indicated that identification of cancer-specific long non-coding RNAs (LncRNAs) could benefit earlier disease detections and improve treatment outcomes in patients suffering from CRC. LncRNAs have raised extensive attentions as they participate in various hallmarks of CRC. The mechanistic evidence gleaned in the recent decade clearly reveals that lncRNAs exert their oncogenic roles by regulating autophagy, epigenetic modifications, enhancing stem phenotype and modifying tumor microenvironment. In view of their pleiotropic functional roles in malignant progression, and their frequently dysregulated expression in CRC patients, they have great potential to be reliable diagnostic and prognostic biomarkers, as well as therapeutic targets for CRC. In the present review, we will focus on the oncogenic roles of lncRNAs and related mechanisms in CRC as well as discuss their clinical potential in the early diagnosis, prognostic prediction and therapeutic translation in patients with this malignancy. Highlights: LncRNAs extensively participate in various hallmarks of CRC. LncRNAs affect the efficacy of chemotherapy and radiotherapy in CRC. Detecting circulating LncRNAs benefits the early diagnosis of CRC. Tumor-derived LncRNAs act as a reliable prognostic biomarkers. LncRNAs can be utilized as primary targets for anti-CRC drug development.